Stability analysis of steel frames with semi-rigid connections and rigid zones by using P-Delta effect - Anh, Vu Quoc (Vietnam Journal of Mechanics, 2002)
Comparing with reinforced concrete structure, member rigidity of steel structure is less, and displacement of steel structure is larger than that of reinforced concrete structure, so the secondary moment due to axial force has to be considered, i e., the problem of P-Delta effect. For most building structures, especially tall steel buildings, the P-Delta effect of most concern occurs in the columns due to gravity load, including dead and live load. The column axial forces are compressive, making the structure more flexible against lateral loads. If compressive P-forces are present and are large enough, the structure may buckle. Local buckling of individual members or global buckling of the whole structure is possible. This paper presents the method to analysis stability of steel frames with semi-rigid connections and rigid zones by using P-Delta effect.